IMF Staff Papers, Volume 50, No. 2 - Flood, Robert (IMF Staff Papers; IMF Staff Papers, 2003)
This paper examines sources of economic growth in East Asia. The conventional growth-accounting approach to estimating the sources of economic growth requires unrealistically strong assumptions about either competitiveness of factor markets or the form of the underlying aggregate production function. The paper outlines a new approach utilizing nonparametric derivative estimation techniques that does not require imposing these restrictive assumptions. The results for East Asian countries show that output elasticities of capital and labor tend to be different from the income shares of these factors. The paper also explores the compensating potential of private intergenerational transfers.